Effects of the publication of Clinical Guidelines for the Management of Chemotherapy-Induced Peripheral Neuropathy on the Administration Preferences of Oncology Specialists: Japanese Association of Supportive Care in Cancer. (19th May 2020) - Hirayama, Yasuo; Yoshida, Yoichiro; Mori, Masanori; Tamura, Kazuo
Abstract: Objective: We conducted a questionnaire survey of oncology specialists to investigate the frequency of administration of different drugs for the management of chemotherapy-induced peripheral neuropathy in Japan in 2015. Our group published Clinical Guidelines for the Management of Chemotherapy-Induced Peripheral Neuropathy in 2017 (CIPN-GL2017). In these guidelines, we recommended duloxetine only. To verify the effect of the publication of the CIPN-GL2017, we conducted a questionnaire survey in 2019. Methods: In 2015 and again in 2019, we investigated the use of vitamin B12, antiepileptic agents, duloxetine, antidepressants other than duloxetine, non-steroidal anti-inflammatory drugs, opioids and the Kampo compound (goshajinkigan) in a questionnaire employing a three-point scale wherein A implies routine or prophylactic administration, B implies occasional administration and C implies infrequent administration. Results: We sent the questionnaires via email to 971 diplomates of the Subspecialty Board of Japanese Society of Medical Oncology in 2015 and 1239 diplomates in 2019. The administration ratio (A + B) of duloxetine for numbness and pain was 46.8 and 31.7%, respectively, in 2015 and 68.9% ( P  < 0.01) and 73.1% ( P  < 0.01) in 2019. In response to the question regarding awareness of the CIPN-GL2017, 53.2% of respondents to the 2019 questionnaire were aware of the CIPN-GL2017. Among the respondents with an awareness of the CIPN-GL2017, the prescription rate of duloxetine (78.3%) for pain was significantly higher than that among respondents without any awareness (67.4%). Conclusions: It is possible that the publication of CIPN-GL2017 influenced administration preferences of oncology specialists. Abstract : We published chemotherapy-induced peripheral neuropathy guidelines in 2017 and conducted questionnaire survey in 2015 and 2019. The administration ratio of duloxetine increased in 2019 by the influence of the guidelines.